TALKING KRISHNA – IMPLEMENTATION OF DATABASE RESPONSIVE SPEECH BUILDER - Budi Berlinton Sitorus (Jurnal Informatika dan Bisnis, 2020)
The Z and Alpha generations are the children who are born in the millennial age, where they cannot avoidlive without gadgets connected to the Internet. Being raised in this era of technological advancement leadsthe children in this generation to have a broad connection without a limit distance. However, languagemay become a barrier. Therefore, the need to be capable in the universal language becomes higher. Thispaper presents the development of an interactive English-language educational game using the voicerecognition technology in Google Assistant. The game is taking Krishna as the main character to attractchildren. The game will give the children the opportunity to dialogue with Krishna. It is hoped that theapplication can train and improve the ability of children to speak English well and correctly. In addition,the introduction of Krishna character can help to deliver the moral values that are presented in Krishna'slife story.Keywords—Google Assistant, Krishna, learning English, story, voice recognition